2020
DOI: 10.7150/jca.37958
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NRON promotes the proliferation, metastasis and EMT process in bladder cancer

Abstract: Background: Bladder cancer (BC) is one of the most common malignancies worldwide with high morbidity and mortality. Long noncoding RNAs (lncRNAs) are thought to play a critical role in cancer development. LncRNA NRON, a repressor of activated T-cell nuclear factor (NFAT), has been shown to be dysregulated in many cancer types. However, the clinical significance and molecular mechanism of NRON in bladder cancer is still unknown. Methods: The expression levels of NRON in BC tissues and cell lines were tested by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…LINC01605 upregulates the expression of matrix MMP9 to promote cell proliferation, migration, and invasion by activating the EMT pathway [ 154 ]. LINC01296 [ 155 ] and NRON [ 156 ] also promote the EMT process in BCa.…”
Section: Emt Processmentioning
confidence: 99%
See 2 more Smart Citations
“…LINC01605 upregulates the expression of matrix MMP9 to promote cell proliferation, migration, and invasion by activating the EMT pathway [ 154 ]. LINC01296 [ 155 ] and NRON [ 156 ] also promote the EMT process in BCa.…”
Section: Emt Processmentioning
confidence: 99%
“…High expression of HOTAIR and CDKN2B-AS is associated with a worse tumor grade. In addition, high expression of 5 lncRNAs positively correlates with tumor stage [ 21 , 23 , 37 , 53 , 54 ], while higher expression of 11 other lncRNAs is related to worse TNM stage [ 52 , 61 , 68 , 70 , 98 , 110 , 128 , 156 , 162 , 182 ]. The expression of 4 lncRNAs is positively associated with an advanced disease stage and poor tumor grade [ 85 , 154 , 191 ].…”
Section: Lncrnas Are Associated With Clinicopathological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of lncRNAs is not only reflected in the growth and development of nerve cells, but more and more studies have revealed the importance of lncRNAs in various central nervous system diseases. NRON is an lncRNA that mediates the cytoplasmic to nuclear transport of NFAT transcription factors [ 39 ]. In animal models, when NRON was removed from the regulation of DSCR1 and DYRK1A genes on chromosome 21, the expressions of DSCR1 and DYRK1A were upregulated, leading to the decrease of NFATc activity, which eventually resulted in characteristics of Down syndrome (DS) [ 40 ].…”
Section: The Regulatory Role Of Lncrnas In the Growth Developmentmentioning
confidence: 99%
“…LncRNA UCA1 was first discovered in bladder cancer and can promote tumor cell proliferation and metastasis. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%